Paths Toward Green Mobility Perspectives on Women and Rail Transport in Bosnia and Herzegovina, and Serbia - Kurshitashvili, Nato (The World Bank, 2022)
This report explores two aspects of the rail transport sector - mobility, and employment--in the countries of Serbia, and Bosnia and Herzegovina from a gender perspective. It examines issues of rail transport for women both as passengers, and as sector employees. It highlights the urgency of transport decarbonization for the Western Balkan countries (WB6) in the context of the European Union's Green Deal,2 which aims to achieve net zero greenhouse gas (GHG) emissions by 2050. This report shows that Covid-19 has decimated rail transport use at a time when global and WB6 regional efforts must dramatically increase their movement toward decarbonization. The study confirms that the pandemic has drawn people away from public transport including rail, and toward more carbon-intensive individual modes of transportation. It also makes a rarely made connection between getting more women into the transport sector and improved mobility for women. Rail services remain male-dominated across the world. The report finds clear parallels between women's employment and mobility. Finally, while this study focuses on women and rail transport, it has the benefit of making rail more attractive for other cohorts as well, including those who primarily use private vehicles (mainly men)
Keywords: Gender; Inequality; Labor Markets; Poverty Reduction; Social Protections and Labor